Martin Mariner - Braas, Nico ([Uitgeverij Lanasta], 2012)
In 1937 The Glen Martin company started with the design of the model I62. This was a design for a twin engine high-wing monoplane flying boat with an inverted gull wing. As power plant one of the most powerful air-cooled radial engines then available was selected: the Wright R-200-6 Cyclone of 1600 hp maximum take-off power.